Long Range Correlated Motions of TIM and their Possible Influence on Enzyme Function - McKinney, J. A.; Deng, Y. T.; George, D. K.; Richard, J.; Markelz, A. G. (Biophysical Journal, 2020)
The alpha-beta barrel structure of triosephosphate isomerase (TIM) is possibly the most common among enzymes. In the case of TIM, structural dynamics are known to be essential to function. In particular the stabilization of the binding pocket by a phosphodianion “handle” of the substrate and the closing of catalytic site loops 6 and 7 over the substrate. Loop 6 moves by as much as 7 Angstroms with binding. Recently a mutant survey for human TIM (hsTIM) found kcat can change significantly for a single mutation distant from the catalytic site. Crystallographic measurements find no structural change with the mutation, suggesting a dynamical mechanism for the allosteric effect. Here we use Stationary Sample Anisotropic Terahertz Microscopy (SSATM) to measure the long-range intramolecular vibrations and determine if specific vibrations couple the allosteric and catalytic sites. SSATM isolated protein long-range structural vibrations based on the dominant displacement direction [1-4]. We examine if specific vibrational bands are associate with loop 6 and loop 7 flexibility.
Keywords: Biophysics

Persistent Protein Motions in a Rugged Energy Landscape Revealed by Normal Mode Ensemble Analysis - Romo, T. D.; Grossfield, A.; Markelz, A. G. (Journal of Chemical Information and Modeling, 2020)
Proteins are allosteric machines that couple motions at distinct, often distant, sites to control biological function. Low-frequency structural vibrations are a mechanism of this long-distance connection and are often used computationally to predict correlations, but experimentally identifying the vibrations associated with specific motions has proved challenging. Spectroscopy is an ideal tool to explore these excitations, but measurements have been largely unable to identify important frequency bands. The result is at odds with some previous calculations and raises the question what methods could successfully characterize protein structural vibrations. Here we show the lack of spectral structure arises in part from the variations in protein structure as the protein samples the energy landscape. However, by averaging over the energy landscape as sampled using an aggregate 18.5 mu s of all-atom molecular dynamics simulation of hen egg white lysozyme and normal-mode analyses, we find vibrations with large overlap with functional displacements are surprisingly concentrated in narrow frequency bands. These bands are not apparent in either the ensemble averaged vibrational density of states or isotropic absorption. However, in the case of the ensemble averaged anisotropic absorption, there is persistent spectral structure and overlap between this structure and the functional displacement frequency bands. We systematically lay out heuristics for calculating the spectra robustly, including the need for statistical sampling of the protein and inclusion of adequate water in the spectral calculation. The results show the congested spectrum of these complex molecules obscures important frequency bands associated with function and reveal a method to overcome this congestion by combining structurally sensitive spectroscopy with robust normal mode ensemble analysis.
Keywords: Chemistry; Computer Science; molecular-dynamics; Pharmacology & Pharmacy; photoactive yellow protein; spectroscopy; state; vibrational-modes

Protein Intramolecular Motions with Deuteration and Inhibitor Binding Dependence - Deng, Y.; McKinney, J.; Romo, T.; Grossfield, A.; Markelz, A. G. (APS R63.003, 2019)

Spectral Assignment of Lysozyme Collective Vibrations - Deng, Y. T.; McKinney, J.; Romo, T.; Grossfield, A.; Markelz, A. (Biophysical Journal, 2019)
Global structural vibrations at terahertz (THz) frequencies have been associated with protein function and allosteric control. A chief obstacle to utilizing this control mechanism has been measurement of specific motions. Recently it was shown that while the vibrational density of states, and isotropic absorption spectra are broad and featureless, collective vibrations can be isolated based on their directionality using aligned samples (realized with protein crystals) and anisotropic THz microscopy [1]. However the assignment of resonant bands to specific structural motions was complicated by the high symmetry of the tetragonal crystals used, and the slow experimental method. To structurally map the vibrations of the chicken egg white lysozyme (CEWL) we measure anisotropic absorption of triclinic crystals using our new technique: ideal polarization varying anisotropic THz microscopy (IPV-ATM). The low symmetry triclinic crystals provide absolute protein orientation, and the near field IPV-ATM rapidly measures broadband terahertz linear dichroism of the microcrystals. All measurements were performed at room temperature under 100% humidity conditions. The unit cell parameters of triclinic lysozyme nitrate crystals, α = 28.5A°, b = 32.7A°, c = 35.1A°, α = 88.2°, β = 108.9°, γ = 111.9°, belonging to the P1 space group, were determined by X-ray diffraction before and after THz measurements. The intramolecular vibrational absorbance of the triclinic crystals has a more complex polarization dependence than the higher symmetry tetragonal crystals, as expected. While the tetragonal crystals have two strong bands at 45cm−1 and 55cm−1, the triclinic crystals have a series of narrow bands between 40 and 60cm−1 and a prominent band at 30cm−1. We compare the measured spectra to normal mode ensemble averaged calculations to assign the observed resonances, and isolating which collective motions impact the catalytic site.
Keywords: Biophysics

Increase in Dynamical Collectivity and Directionality of Orange Carotenoid Protein in the Photo-Protective State - Deng, Y. T.; Luck, C. H.; Romo, T. D.; Grossfield, A. M.; Bandara, S.; Ren, Z.; Yang, X. J.; Markelz, A. G. (Biophysical Journal, 2018)
Keywords: Biophysics

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

The role of the protein surface on the local biological water dynamics - Liang, W.; He, Y. F.; George, D.; Markelz, A. G. (Biosensing Ii, 2009)
Protein function is reliant on structural flexibility and this flexibility is slaved to the surrounding solvent. Here we discuss how the exposed surface of the protein influences the solvent dynamics and thereby influences the protein's own structural dynamics. We discuss measurements of the THz absorption of water in the presence of hydrophilic and hydrophobic surfaces.
Keywords: alanine; dynamics; hydration; lysine; lysozyme; proteins; relaxation; spectroscopy; Terahertz; thz

Terahertz response of quantum point contacts - Song, J. W.; Kabir, N. A.; Kawano, Y.; Ishibashi, K.; Aizin, G. R.; Mourokh, L.; Reno, J. L.; Markelz, A. G.; Bird, J. P. (Applied Physics LettersApplied Physics LettersApplied Physics Letters, 2008)
We measure a clear terahertz response in the low-temperature conductance of a quantum point contact at 1.4 and 2.5 THz. We show that this photoresponse does not arise from a heating effect, but that it is instead excellently described by a classical model of terahertz-induced gate-voltage rectification. This effect is distinct from the rectification mechanisms that have been studied previously, being determined by the phase-dependent interference of the source drain and gate voltage modulations induced by the terahertz field. (C) 2008 American Institute of Physics.
Keywords: detector; devices; field-effect transistors; Physics; plasma-waves; radiation; resonant detection; subterahertz; transport

Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz

Direct measurements of optical phonons in SrTiO3 nanosystems - Wolpert, D; Korolev, K; Sachs, S; Knab, J; Cox, W; Cerne, J; Markelz, A.G; Zhao, T; Ramesh, R; Moeckly, B.H (Physica E: Low-dimensional Systems and Nanostructures, 2003)
We use terahertz time domain spectroscopy to examine finite size effects on the optical phonon modes in SrTiO3 thin films. In temperature-dependent measurements we find a near absence of mode softening in the TO1 phonon frequency. Furthermore we see an increase in the soft mode frequency with reduced thickness. Both of these results correlate well with the reduced dielectric response observed for nanoscale ferroelectric systems.
Keywords: Ferroelectrics; Finite size; Mode softening; phonons; Strontium titanate; Terahertz

Finite size effects in ferroelectric nanosystems: Absence of mode softening - D. Wolpert; W. Cox; J. Cerne; A. Markelz; T. Zhao; R. Ramesh (2003 Nanotechnology Conference and Trade Show - Nanotech, 2003)
We present measurements of the mode softening behavior for PbZr 0.5Ti0.5O3 (PZT(50)) thin films using terahertz time domain spectroscopy (TTDS). The films were grown using pulsed laser deposition (PLD) techniques on silicon substrates to study how reduced size affects the mode softening behavior. At room temperature two modes are observed at 1.1 THz (37 cm-1) and at 2.3 THz (77 cm-1). As the temperature is increased toward Tc we do not see strong mode softening, but rather a spectral weight transfer from the high frequency mode to the low frequency mode. This absence of mode softening is more dramatic than that reported by other investigators[1]. We will discuss the possible sources for this discrepancy. These results suggest a change in lattice dynamics for nanoscale ferroelectric films that may be highly dependent on the sample preparation technique.
Keywords: Ferroelectric materials; Fourier Transform Infrared Spectroscopy; Frequency ranges; Lead compounds; Mode softening; nanostructured materials; Natural frequencies; Optical modes; Permittivity; phase transitions; phonons; Routers; Thermal effects

Pulsed terahertz spectroscopy of DNA, bovine serum albumin and collagen between 0.1 and 2.0 THz - Markelz, A. G.; Roitberg, A.; Heilweil, E. J. (Chemical Physics Letters, 2000)
We report the first use of pulsed terahertz spectroscopy to examine low-frequency collective vibrational modes of biomolecules. Broadband absorption increasing with frequency was observed for lyophilized powder samples of calf thymus DNA, bovine serum albumin and collagen in the 0.06-2.00 THz (2-67 cm(-1)) frequency range, suggesting that a large number of the low-frequency collective modes for these systems are IR active. Transmission measurements at room temperature showed increasing FIR absorption with hydration and denaturing. (C) 2000 published by Elsevier Science B.V. All rights reserved.
Keywords: b-dna; Chemistry; films; modes; Physics; proteins

Terahertz grid frequency doublers - Chiao, Jung-Chih; Markelz, Andrea; Li, Yongjun; Hacker, Jonathan; Crowe, Thomas; Allen, James; Rutledge, David (Proc. Sixth Intl. Symp. Space Terahertz Tech, 1995)

PROBING TERAHERTZ DYNAMICS IN SEMICONDUCTOR NANOSTRUCTURES WITH UCSB FREE-ELECTRON LASERS - Allen, S. J.; Craig, K.; Felix, C. L.; Guimaraes, P.; Heyman, J. N.; Kaminski, J. P.; Keay, B. J.; Markelz, A. G.; Ramian, G.; Scott, J. S.; Sherwin, M. S.; Campman, K. L.; et al. (Journal of Luminescence, 1994)
The UCSB free-electron lasers provide kilowatts of continuously tunable radiation from 120 GHz to 4.8 THz. They have the most impact on terahertz science and technology that require a tunable, high power source to explore non-linear dynamics or that sacrifice incident power to recover the linear response of systems with very small cross-section. We describe three experiments that demonstrate the utility of these lasers in experiments on the terahertz dynamics of semiconductor nanostructures: (i) terahertz dynamics of resonant tunneling diodes, (ii) saturation spectroscopy of quantum wells and (iii) photon-assisted tunneling in superlattices.